Mobile Usage baskets to measure ICT Sector Performance - Stephen Esselaar; Christoph Stork (International Telecommunications Society (ITS), 2018)
This paper aims to address two questions. Firstly, whether the OECD mobile usage baskets from December 2017 are suitable tools to measure ICT sector performance in developing countries and, secondly, to identify issues that require a regulatory or policy response. This paper uses prices collected in January 2018 from 100 countries, 547 mobile operators and 2560 prepaid products from the Global South to assess the suitability of the OECD basket methodology for ICT policy making and regulation. We propose a simple index that can be compiled using ITU data to measure the drivers of the separation of mobile access and service platforms.
Keywords: 330